2014
DOI: 10.1007/s10734-014-9788-z
|View full text |Cite
|
Sign up to set email alerts
|

The link between high-impact practices and student learning: some longitudinal evidence

Abstract: The current paper used data from the Wabash National Study of Liberal Arts Education-a longitudinal, pretest/posttest design-to estimate the effects of participation in the ten ''high-impact'' educational practices put forth and endorsed by the Association of American Colleges and Universities (AAC&U) on a variety of liberal arts educational outcomes. The high-impact practices included in the study were: first-year seminars, academic learning communities, writing-intensive courses, active and collaborative lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
235
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(252 citation statements)
references
References 38 publications
10
235
0
7
Order By: Relevance
“…Concerning the individual four high-impact pedagogies incorporated in this analysis, Kilgo, Sheets, and Pascarella (2015), using the Wabash National Study of Liberal Arts Education, conducted analyses on over 2,000 students from 17 four-year institutions. Participation in research was associated with gains on critical thinking, interest in lifelong learning, need for cognition, two measures of intercultural effectiveness, and socially responsible leadership.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the individual four high-impact pedagogies incorporated in this analysis, Kilgo, Sheets, and Pascarella (2015), using the Wabash National Study of Liberal Arts Education, conducted analyses on over 2,000 students from 17 four-year institutions. Participation in research was associated with gains on critical thinking, interest in lifelong learning, need for cognition, two measures of intercultural effectiveness, and socially responsible leadership.…”
Section: Discussionmentioning
confidence: 99%
“…Future research needs to investigate the extent to which integrating these pedagogies into well-designed and well-implemented hybrid courses reproduces these results, exceeds these results, and/or produces other learning outcomes (e.g., civic learning, personal growth). Kilgo et al (2015) attempted to control for some pre-existing variables, but generally research on service-learning and high impact practices suffers from a major confounding variable: self-selection of students into these educational experiences. For example, Eyler, Giles, and Braxton (1997) found that students who chose service-learning differed from those who did not on pre-service attitudes, skills, values, and understanding of social issues.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, earlier involvement in research and longer time periods of research involvement have been shown to promote continued coursework and majoring in CS (Russell et al, 2007;Tashakkori et al, 2011). Overall, quality research participation has positive effects on students' skills and retention in STEM (Kilgo et al, 2015;see Barker, 2009), with some evidence suggesting stronger benefits for underrepresented students (Lopatto, 2007). Programming opportunities that engage students in research within and across disciplines can be used to increase high quality experiences that engage students in both programming and STEM.…”
Section: Discussionmentioning
confidence: 99%
“…Segundo, asociar la buena docencia a un profesor que hace ciertas cosas que la universidad le pide que haga. Y tercero, asociar la buena docencia a que el profesor logre que sus estudiantes aprendan, es decir, valorar al profesor que centra su enseñanza en el estudiante y la orienta hacia el aprendizaje (Entwistle et al, 2000;Kyriakides et al, 2013;Kilgo et al, 2014).…”
Section: Introductionunclassified